Manajemen “Kurikulum Langit” dalam menguatkan pendidikan karakter siswa - Ivan Supangat; Nan Rahminawati; Bambang Saiful Ma'arif (Idarotuna: Jurnal Manajemen Pendidikan Islam, 2024)
The purpose of this study was to determine the management of a special curriculum in an educational institution in strengthening students' character. Programmed management will be able to optimize educational institutions in achieving learning goals to produce students with positive character. The location of the study was at SD Juara, East Jakarta. The special curriculum that was implemented was named "Kurikulum Langit". The method used in this study was descriptive qualitative. Data collection was carried out through interviews, observations and documentation studies. From the results of the study, it was found that the management of the "Kurikulum Langit" consists of the planning, organizing, implementing and supervising processes. Curriculum planning goes through the stages of compiling objectives, internalization plans for the work culture of educators and education personnel, developing a special curriculum and designing learning programs. The organization is carried out by the principal by forming a curriculum development team, program coordinator, making a decree and distributing tasks involving homeroom teachers and teachers. The implementation process at the school, class and home levels is through the process of exemplary behavior, instilling values, habituation and enforcing rules. The implementation involves parents such as in the maghrib pengajian program, mabit keluarga, lukman berilmu and parenting school. While the supervision process is carried out by conducting periodic supervision and evaluation of the “Sky Curriculum” that has been implemented and evaluating the obstacles experienced in implementing the curriculum. The positive impact of the curriculum is seen in the character of students who reflect the values ​​of the 7 Champion Habits of the “Sky Curriculum”.